Topology, landscapes, and biomolecular energy transport - Justin E. Elenewski (Nature Portfolio, 2019)
Understanding vibrational energy transfer in macromolecules has been challenging to both theory and experiment. Here the authors use non-equilibrium molecular dynamics to reveal the relationship between heat transport in a model peptide, emergent nonlinearity, and the underlying free energy landscape.